Chagas Disease and Heart Failure: An Expanding Issue Worldwide - Felipe Martinez (Radcliffe Medical Media, 2019)
Chagas disease, originally a South American endemic health problem, is expanding worldwide because of people migration. Its main impact is on the cardiovascular system, producing myocardial damage that frequently results in heart failure. Pathogenic pathways are mainly related to inmunoinflamatory reactions in the myocardium and, less frequently, in the gastrointestinal tract. The heart usually shows fibrosis, producing dilatation and damage of the electrogenic cardiac system. These changes result in cardiomyopathy with heart failure and frequent cardiac arrhythmias and heart blocks. Diagnosis of the disease must include a lab test to detect the parasite or its immune reactions and the usual techniques to evaluate cardiac function. Therapeutic management of Chagas heart failure does not differ significantly from the most common treatment for dilated cardiomyopathy, with special focus on arrhythmias and several degrees of heart block. Heart transplantation is reserved for end-stage cases. Major international scientific organisations are delivering recommendations for prevention and early diagnosis. This article provides an analysis of epidemiology, prevention, treatment and the relationship between Chagas disease and heart failure.